Structural Investigation of Hesperetin-7-O-Glucoside Inclusion Complex with β-Cyclodextrin: A Spectroscopic Assessment - Kapoor, Mahendra P.; Moriwaki, Masamitsu; Minoura, Katsuhiko; Timm, Derek; Abe, Aya; Kito, Kento (Molecules (Basel, Switzerland), 2022)
Flavonoids are biologically active natural products of great interest for their potential applications in functional foods and pharmaceuticals. A hesperetin-7-O-glucoside inclusion complex with β-cyclodextrin (HEPT7G/βCD; SunActive® HCD) was formulated via the controlled enzymatic hydrolysis of hesperidin with naringinase enzyme. The conversion rate was nearly 98%, estimated using high-performance liquid chromatography analysis. The objective of this study was to investigate the stability, solubility, and spectroscopic features of the HEPT7G/βCD inclusion complex using Fourier-transform infrared (FTIR), Raman, ultraviolet–visible absorption (UV–vis), 1H- and 13C- nuclear magnetic resonance (NMR), differential scanning calorimetry (DSC), liquid chromatography/mass spectroscopy (LC–MS), scanning electron microscopy (SEM), and powdered X-ray diffraction (PXRD) spectroscopic techniques including zeta potential, Job’s plot, and phase solubility measurements. The effects of complexation on the profiles of supramolecular interactions in analytic features, especially the chemical shifts of β-CD protons in the presence of the HEPT7G moiety, were evaluated. The stoichiometric ratio, stability, and solubility constants (binding affinity) describe the extent of complexation of a soluble complex in 1:1 stoichiometry that exhibits a greater affinity and fits better into the β-CD inner cavity. The NMR spectroscopy results identified two different configurations of the HEPT7G moiety and revealed that the HEPT7G/βCD inclusion complex has both –2S and –2R stereoisomers of hesperetin-7-O-glucoside possibly in the –2S/–2R epimeric ratio of 1/1.43 (i.e., –2S: 41.1% and –2R: 58.9%). The study indicated that encapsulation of the HEPT7G moiety in β-CD is complete inclusion, wherein both ends of HEPT7G are included in the β-CD inner hydrophobic cavity. The results showed that the water solubility and thermal stability of HEPT7G were apparently increased in the inclusion complex with β-CD. This could potentially lead to increased bioavailability of HEPT7G and enhanced health benefits of this flavonoid.